Distinct Expression of miR-378 in Nonsyndromic Cleft Lip and/or Cleft Palate: A Cogitation of Skewed Sex Ratio in Prevalence. (January 2021) - Xu, Yuzi; Xie, Binbin; Shi, Jue; Li, Jia; Zhou, Chuan; Lu, Wei; Xu, Fengqin; He, Fuming
Objective: Nonsyndromic cleft lip and/or cleft palate (NSCL/P) is an isolated phenotype of orofacial clefts with skewed sex ratio in prevalence. This study aims to identify differentially expressed genes (DEGs) and microRNAs (DEMs) of NSCL/P by integrated bioinformatics analysis, revealing mechanisms for sexual dimorphism in prevalence. Materials and Methods: First, we downloaded the expression profile data from Gene Expression Omnibus database to identify DEGs and DEMs. Second, Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses performed DEGs' functions. Then, clustered DEGs were identified through protein–protein interaction networks. Combining clustered DEGs with key genes searched in GeneCards enlarged NSCL/P-related genes. Moreover, the genes were linked by transcription factors (TFs). Subsequently, connected by the above TFs, DEMs and genes were used to establish the miRNA-TF-messenger RNA (mRNA) regulatory networks. Results: The DEGs in sex-ignored group, female-only group, and male-only group were obtained, respectively. Among the DEMs, miR-378 was downregulated in females but upregulated in males. In female-only group, the miRNA-TF-mRNA regulatory networks showed miR-378-SP1-POLE2/CDK6/EZR regulatory axis was found to be key candidates of NSCL/P. Conclusions: Our findings suggest that different expression of miR-378 is consistent with the skewed sex ratio in the prevalence of NSCL/P.